Indonesian Migrant Workers, Double Job Double Risk: Commodification of Life Content - Amelia, Syfa; Elisabeth Adventa Galuh, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Indonesian migrant workers currently have a new trend as part-timer content creators in social media, documenting their life and making videos or live videos about their life in a new country. This is common thing between the diaspora to document their lives in a different country, but there is a gap that differentiates between diaspora or white-collar immigrants from Indonesian migrant workers who commonly work as unskilled laborers. As we already know how policies that protect immigrants do not really work because of the high case of immigrant abuse, intimidation, persecution, low welfare, etc. Immigrants seeing the potential of being content creators in social media will give them better welfare and life quality when actually they become new commodities by creating content about their life. Using Pierre Bourdieu theory of modal commodification, we conduct exploratory research to investigate problems about commodification content that is not clearly defined. The first step we do is doing observations of migrant workers content creators and then we do online research and literature research to strengthen our research on a specific case that is Zhiee Leely and Maybe Memeyon Youtube. The results show us that Indonesian migrants worker are unconsciously being commodified in a habitus that leads them to get financial modal by-product daily content on Youtube and it is mean they need to do a double job, longer working hours, more risks, without government social security because only being migrants worker for them did not guarantee them better life better welfare. Keywords: migrant workers, double commodification, welfare, social media, content creator.